Multisystemic Langerhans cell histiocytosis: case report - Larissa A. Paiva; Daniela M. Takano; Valeska A. S. Queiroz; Laís S. Príncipe
ABSTRACT Langerhans cell histiocytosis is the designated name for a spectrum of rare diseases that affects children from one- to three-years-old, which name refers to the proliferation of cells morphologically and immunophenotypically similar to the specialized dendritic cells of the skin and mucosa (Langerhans cells). This article reports a case of multisystemic Langerhans cell histiocytosis diagnosed by autopsy of a four-day newborn with confirmation by immunohistochemistry and secondary systemic infection associated.